The Population of NuSTAR Black Hole X-Ray Binaries - Paul A. Draghis; Jon M. Miller; Laura Brenneman; Elisa Costantini; Luigi C. Gallo; Mark Reynolds; John A. Tomsick; Abderahmen Zoghbi (The Astrophysical Journal)
The spin of a black hole (BH) encodes information about its formation and evolution history. Yet the understanding of the distribution of BH spins in X-ray binaries (XBs), of the models used to measure spin, and of their impact on systematic uncertainties remains incomplete. In this work, we expand on previous analyses of the entire NuSTAR archive of accreting BH XBs. Prior work compiled a sample of 245 spectral fits using the relativistic reflection method for NuSTAR observations of 36 BH systems. Here, we aim to probe two aspects: the connection between BH spin and binary system properties, and the relationships between parameters in the spectral fits. We identify moderate negative correlations between spin uncertainty and both BH mass and system inclination, and a moderate positive correlation with distance. We also point out tentative multidimensional degeneracies between inclination, disk density, Fe abundance, ionization, and the presence or absence of absorption features from ionized outflows linked to disk winds. Lastly, we provide a comprehensive view of the observed distribution of BH spins in XBs, in comparison to spins inferred from gravitational waves. We find that the distribution of BH spins in XBs can be described by a beta distribution with α = 5.66 and β = 1.09. This data set is highly complex, and the analysis presented here does not fully explore all potential parameter correlations. We make the full data set available in Zenodo to the community to encourage further exploration.